Optimizing Inventory Management of Perishable Goods: Joint Pricing and Ordering Policies with Deterioration and Lifetime Considerations - Anitadevi Yadav; Harsh Vardhan; Niranjan Potadar (Utilitas Mathematica, 2025)
Effective management of perishable goods is essential for businesses in industries such as food, pharmaceuticals, and chemicals, where products have a limited shelf life. This paper explores joint pricing and ordering policies as critical strategies for optimizing inventory management while considering deterioration and product lifetime. Traditional inventory management strategies are insufficient for perishable goods, where rapid value decline requires businesses to employ dynamic pricing models that align with optimal stock levels. This study delves into various deterioration models, including those of Ghare and Schrader (1963) and Aggarwal and Jaggi (1989), as well as recent advancements like ramp-type demand and flexible replenishment policies. The paper highlights the importance of real-time data, supply chain coordination, and trade credit financing in addressing the unique challenges posed by perishable goods management. Furthermore, it underscores the need for integrated decision-making to reduce waste and enhance sustainability. By implementing dynamic pricing systems and adjusting order quantities based on demand and product condition, businesses can minimize losses due to spoilage while maximizing profitability and customer satisfaction.